2011
DOI: 10.1097/ijg.0b013e3181e080ef
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Findings in Early Encapsulated Blebs of Young Patients Treated With the Ahmed Glaucoma Valve

Abstract: Encapsulation of the AGV is an early complication in young patients, leading to inhibition of fluid exchange and failure of the procedure. The valve mechanism is blocked by contracted scar tissue, but the device itself is not affected by the encapsulation. Surgical excision of the capsule immediately leads to an aqueous flow and drop of intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 12 publications
5
36
0
2
Order By: Relevance
“…In the control group, the inner layer of the fibrous capsule was compact collagen fibers characterized by transdifferentiation of fibroblasts into myofibroblasts, and the outer layer of the fibrous capsule was vascularized. These results were consistent with those of Thieme et al [3], who reported histopathological findings of encapsulated blebs around AGVs.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In the control group, the inner layer of the fibrous capsule was compact collagen fibers characterized by transdifferentiation of fibroblasts into myofibroblasts, and the outer layer of the fibrous capsule was vascularized. These results were consistent with those of Thieme et al [3], who reported histopathological findings of encapsulated blebs around AGVs.…”
Section: Discussionsupporting
confidence: 83%
“…Another experimental study reported that the thinner and more vascular capsule formed by a modified AGV with expanded polytetrafluoroethylene may result in decreased resistance to aqueous egress compared with avascular fibrous encapsulation [29]. Therefore, in the study group, the dilated blood vessels located throughout a thin and loose fibrous capsule might be more effective for fluid transport through the capsular wall than in the control group [3,29,30]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations